2020
DOI: 10.1002/adfm.202000883
|View full text |Cite
|
Sign up to set email alerts
|

2D MXenes for Electromagnetic Shielding: A Review

Abstract: Since the first report on electromagnetic interference (EMI) shielding of 2D Ti 3 C 2 T x in 2016, MXenes have captured the leadership position among lightweight shielding materials due to many advantages, including their excellent shielding performance, outstanding metallic conductivity, low density, large specific surface area, tunable surface chemistry, and solution processability. MXenes triggered a huge interest in the materials research community, leading to over 100 reported publications on MXenes' EMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
405
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 547 publications
(405 citation statements)
references
References 73 publications
0
405
0
Order By: Relevance
“…owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample. Currently, a lot of attention have been paid to understand the mechanical and tribological properties of assorted MXenes and their composites under different conditions such as functionalization groups, varied loading and environmental conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample. Currently, a lot of attention have been paid to understand the mechanical and tribological properties of assorted MXenes and their composites under different conditions such as functionalization groups, varied loading and environmental conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, various properties of MXenes have been revealed by both theoretical simulations and experimental investigations, predicting that they can be significantly influenced by their intrinsic compositions and post‐treatments. Consequently, 2D MXene materials have been extensively used in various fields, such as energy storage devices, [ 34 ] biomedicine, [ 49 ] EMI shieldings, [ 37 ] catalysts, [ 31 ] sensors, [ 20 ] and other fields. [ 14,29 ] The property modifications of MXenes are still ongoing to further enhance the performance of MXene‐based devices.…”
Section: Preparations and Properties Of Mxenesmentioning
confidence: 99%
“…[ 33–36 ] In addition, MXenes are used for electromagnetic interference (EMI) shielding owing to their excellent electronic conductivity. [ 37–39 ] Furthermore, the unique optical response makes MXenes promising materials in the areas of nonlinear photonics, [ 40–45 ] saturable absorbers, [ 46–48 ] photothermal therapy, [ 49–52 ] field effect transistors, [ 53 ] as well as photocatalysts. [ 54–56 ] However, the development of pristine MXenes has been impeded due to several drawbacks such as inevitable restacking, large contact resistance, low flexibility, and poor stability in oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The miniaturization of modern electronic devices and circuits has given rise to rapid growth in the electronic systems, while these miniaturized devices, more or less, generate undesirable electromagnetic interference that has detrimental effects on human health, such as cancer, [224] nausea, [225] eye problems, [226] and adverse influences on infant brain development. [227,228] MXenes almost have all the fundamental characteristics which are extremely essential in an EMI shielding material, that is, light weight, large specific surface area, flexibility, excellent electrical conductivity, and ease of processability, [27,229] and functional 2D MXenes offer multiple internal reflections of the electromagnetic radiation, which can further improve the EMI shielding efficiency.…”
Section: Emi Shieldingmentioning
confidence: 99%